Revisão do gênero Anisocerus Lepeletier & Audinet-Serville, 1830 (Coleoptera, Cerambycidae, Lamiinae, Anisocerini) - Julio, Carlos Eduardo De Alvarenga [UNESP] (Sociedade Brasileira De Entomologia, 2003)
The genus Anisocerus and the two species, A. scopifer (Germar, 1824) and A. stellatus Guérin-Ménéville, 1855, are redescribed and illustrated. A new synonym is proposed: A. stellatus Guérin-Méneville, 1855 = A. onca White, 1855 syn. nov. The two species are redescribed and illustrated.
Revision of the genus Anisocerus Lepeletier & Audinet-Serville, 1830 (Coleoptera, Cerambycidae, Lamiinae, Anisocerini)
Keywords: Anisocerini; Anisocerus; Cerambycidae; Neotropical